2018
DOI: 10.1002/aelm.201800407
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Resistive Switching Dynamics in BaTiO3 Tunnel Junctions

Abstract: microstructural effects should play a major role on the time-dependent dynamics of the polarization switching. [23][24][25] Most commonly, asymmetric electrodes exist in ferroelectric capacitors either because of different metals are used or because the nature of the corresponding metal/ferroelectric and ferroelectric/metal interfaces is different. Thus, asymmetric polarization switching for the positive and the negative bias can occur, as experimentally observed. [22,[26][27][28][29][30] When referring to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
(85 reference statements)
3
16
1
Order By: Relevance
“…3a, b), makes indiscernible the electronic and ionic transport channels. Analogous abrupt change of resistance at V W < 0 was reported in other BTO-based FTJs 53,60 and it was interpreted in terms of ferroelectric domain avalanches stimulated by the asymmetric voltage drop across the junctions. Now, we turn to the electrical characterization of the FTJs under illumination conducted by using blue (λ = 405 nm, E = 3.06 eV) and red (λ = 638 nm, E = 1.94 eV) lasers, near and well below BTO bandgap (E g = 3.3 eV) 61 , respectively.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…3a, b), makes indiscernible the electronic and ionic transport channels. Analogous abrupt change of resistance at V W < 0 was reported in other BTO-based FTJs 53,60 and it was interpreted in terms of ferroelectric domain avalanches stimulated by the asymmetric voltage drop across the junctions. Now, we turn to the electrical characterization of the FTJs under illumination conducted by using blue (λ = 405 nm, E = 3.06 eV) and red (λ = 638 nm, E = 1.94 eV) lasers, near and well below BTO bandgap (E g = 3.3 eV) 61 , respectively.…”
Section: Resultssupporting
confidence: 75%
“…3a, b ), makes indiscernible the electronic and ionic transport channels. Analogous abrupt change of resistance at V W < 0 was reported in other BTO-based FTJs 53 , 60 and it was interpreted in terms of ferroelectric domain avalanches stimulated by the asymmetric voltage drop across the junctions.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…It has also been shown that by performing minor polarization loops, ferroelectric tunnel devices can store information in different resistive states, mimicking the functioning of a memristive element. [4,5] This approach has been successfully achieved by using ferroelectric perovskites such as BaTiO 3 , [6][7][8][9] Pb(Zr 0.2…”
mentioning
confidence: 99%
“…Hence, the device simultaneously containing the resistive switching characteristics and rectification effect is desirable to resolve the conflict between sneak path problems and integration complexity.Resistive switching characteristics have been extensively studied in different materials, such as semiconductor oxides, [5][6][7][8] perovskites, [9,10] chalcogenides, [11][12][13][14][15] and ferroelectrics. [16,17] Although metal oxides have attracted much attention in volatile memory technology but the nonuniformity and stability issues diverted the attention of researchers to other materials. The electric field induced switchable spontaneous polarization in ferroelectric thin films make them a promising candidates for nonvolatile memories.…”
mentioning
confidence: 99%